Factors influencing consumers’ intention towards online grocery shopping for Tesco Malaysia - Pauzi, Siti Fatin Fatehah (2017)
Nowadays, Internet is one of the most popular platforms for people to do online shopping include grocery items. Many studies have been conducted to investigate the determinants of customer intentions for online grocery shopping. Till now, there is no consensus on what are the factors that actually influencing people to shop grocery items through Internet. This paper aims to explore the factors including social influences, facilitating conditions, hedonic motivations, financial risk and perceived trust which influence the consumer intention to purchase grocery online. From the literature review, this paper found that many studies have investigated numerous factors for purchase intention, especially, in the cases which fashion and trends are involved. However, few studies have focused on the factors that affect consumers’ intention to online grocery shopping particularly in Malaysia. A total of 400 questionnaires were distributed to the virtual community of Tesco Malaysia using private message. Multiple regression was used to test the relationships between motivational factors and purchase intention of grocery products. The results show that social influences, facilitating conditions, hedonic motivations and perceived trust are positively related to consumers’ intention to purchase grocery online. However, financial risk has no impact on the purchase intention. This can be explained that the risk of online shopping is reduced due to the popularity of online shopping nowadays and also online consumers have more confident about the security of e-commerce business transaction. Theoretical and managerial implications, as well as suggestions for future researches and limitations are discussed.